2008
DOI: 10.1590/s1806-83242008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of method and period of storage on the microtensile bond strength of indirect composite resin restorations to dentine

Abstract: This study evaluated the influence of the method and period of storage on the adhesive bond strength of indirect composite resin to bovine dentin. Ninety bovine incisors were stored in three different solutions: 0.2% thymol, 10% formalin, and 0.2% sodium azide, during 3 periods of storage: 7 days, 30 days and 6 months, resulting in 9 groups (n = 10). The roots were cut off and the buccal surface was ground with #600-grit silicon carbide paper. The surface was conditioned with 37% phosphoric acid for 15 s and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…The 0.1% thymol solution was used for infection control of extracted teeth because it is a topical antiseptic and mold growth inhibitor 16) . It has been reported that thymol solution has no influence on bond strength when teeth are stored for up to 6 months 17) . The stored teeth in this study were used for testing within one month of preparation.…”
Section: Tooth Specimen Preparationmentioning
confidence: 99%
“…The 0.1% thymol solution was used for infection control of extracted teeth because it is a topical antiseptic and mold growth inhibitor 16) . It has been reported that thymol solution has no influence on bond strength when teeth are stored for up to 6 months 17) . The stored teeth in this study were used for testing within one month of preparation.…”
Section: Tooth Specimen Preparationmentioning
confidence: 99%
“…The remaining 25 studies, which we included, evaluated the following parameters: 1) in relation to specimens: geometric aspects [5][6]9,[11][12][13][14][15][16][17][18][19][20][21] cutting speed [22][23] , cutting method 24 , wear-and-tear and integrity method after cutting 23 , storage time 22 , inclusion of specimens with premature failure 24 , imperfection during manufacture 16 , bonding surface area 5,[19][20]25 , wear-and-tear method for the dentin 26 , form of filling and fixing 6,15,19;27 ; 2) storage time of teeth used in the assay 28 ; 3) angle of the bond interface 29 ; 4) incline of the dentin walls 30 ; 5) variation in adhesive resistance between the teeth or within the same tooth 31 ; 6) adhesive thickness 30 ; 7) use of the cohesive resistance of dentin near the bonding interface as a standard of reference 18 ; 8) loading speed during the test 19,32 ; 9) thickness of remaining dentin 19 ; 10) imperfections in the adhesive layer 16 . The characteristics of the included studies are summarized in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have made suggestions for how to obtain a more precise test that would optimize the stress distribution on the adhesive interface and allow comparison across studies. For example, adhesive resistance and stress distribution on the resin-dentin interface could be improved by: storing teeth to be used as sources of specimens for no more than 30 days in thymol or formalin 28 ; standardizing the cutting speed, giving preference to higher speeds, so as to produce less disk oscillation and reduce specimen surface damage [22][23] ; cutting with diamond-impregnated thread to maintain specimen integrity 24 ; using stick-shaped specimens at least 1.5 mm thick in enamel bonding tests 6 ; testing the bonding to dentin using stick-shaped 9,14,17,23 , dumbell 21 or hourglass-shaped specimens 7 with a 1-mm 2 adhesive area and a 1-mm radius of curvature for the notch 35 ; fixing specimens at both ends 6,15,27 ; storing specimens for no more than a week in distilled water 22 ; using a notched jig 19 ; using sandpaper to wear dentin instead of burs 26 ; and not using specimens with steeply inclined bond interface 29 . However, even with standardization of some microtensile strength test parameters, the mechanics of laboratory tests on biological substrates with enamel and dentin remain highly variable, especially with respect to dentin's dynamic characteristic that is, its differences in mineral content, tubular density, and collagen orientation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…1e16 A steam autoclave, chemical heat sterilization, dry heat, g radiation, ethylene oxide, and freezing are also used as methods of storage. 2,8,14,17 The period of storage, which ranges from a few hours to years 1,5,12,15,18 and the frequency at which the solution is changed 18 are other factors which may affect the storage process.…”
Section: Introductionmentioning
confidence: 99%